TINJAUAN PROSEDUR PENGAJUAN KPR PADA BANK BTN KCP CIAMIS - Muhamad Rafi Alpariz; Asep Dadan Suhendar (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
This study aims to review and describe the procedure for applying for Home Ownership Credit (KPR) at Bank BTN Sub-Branch Office (KCP) Ciamis. KPR is one of the banking financing products designed to help people own a house through a credit system with a certain period. In its implementation, the KPR application process requires systematic procedural stages and the application of prudential principles to minimize the risk of non-performing loans. The research method used in this study is a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation with related parties at Bank BTN KCP Ciamis, particularly in the Consumer Loan Sales section. This study focuses on the stages of the KPR application procedure, which include interviews, credit analysis, data entry, issuance of the Credit Approval Letter (SP3K), credit binding (contract/akad), and fund disbursement. The results of the study indicate that the KPR application procedure at Bank BTN KCP Ciamis has been implemented quite well. The stages of interviews, credit analysis, issuance of SP3K, credit binding, and fund disbursement have been carried out properly, while at the data entry stage there are still minor administrative constraints such as data revisions due to discrepancies in customer information. In addition, other obstacles faced in the KPR application process include incomplete customer documents and delays in document submission from developers or notaries. Overall, the implementation of the KPR application procedure at Bank BTN KCP Ciamis has been running fairly well and in accordance with the prudential banking principle. However, improvements in administrative accuracy and coordination with external parties are still needed to ensure that the credit application process becomes more effective and efficient.